2009
DOI: 10.1039/b907264k
|View full text |Cite
|
Sign up to set email alerts
|

Formation of conjugated polymer brushes by surface-initiated catalyst-transfer polycondensation

Abstract: Electroactive conjugated polymer brushes of poly(thiophene) and poly(phenylene) have been prepared via a surface-initiated Kumada-type polycondensation reaction, yielding films with a thickness up to 42 nm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
105
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(106 citation statements)
references
References 23 publications
0
105
1
Order By: Relevance
“…It was also demonstrated that the SI-KCTP from functional block copolymers is a promising tool to nanostructure thin films with polymer brushes (Scheme 11). Sontag et al [49] and Marshall et al [50] used mixtures of Ni(cod) 2 and phosphorous ligands to generate Ni(0) species Scheme 11. Approaches to surface-initiated KCTP: grafting from P4VP-b-PS(I) adsorbed on silica surfaces.…”
Section: Polymer Brushes and Surface Initiated Polymerizationmentioning
confidence: 99%
“…It was also demonstrated that the SI-KCTP from functional block copolymers is a promising tool to nanostructure thin films with polymer brushes (Scheme 11). Sontag et al [49] and Marshall et al [50] used mixtures of Ni(cod) 2 and phosphorous ligands to generate Ni(0) species Scheme 11. Approaches to surface-initiated KCTP: grafting from P4VP-b-PS(I) adsorbed on silica surfaces.…”
Section: Polymer Brushes and Surface Initiated Polymerizationmentioning
confidence: 99%
“…Then, lauryl methacrylate monomers were clicked onto the monoliths using either heat or UV initiation. Thiol-yne and CuAAC reactions were also utilized to achieve reactive porous polymer monoliths [8,124]. Zhang and coworkers produced poly(glycidyl methacrylate-codivinylbenzene), poly(GMA-co-DVB), and poly(vinylbenzyl chloride-codivinylbenzene), (poly(VBC-co-DVB), monoliths to provide the reactive sites for click chemistry [29].…”
Section: Polymeric Monolithic Columnsmentioning
confidence: 99%
“…The preparation of such high-molecular-weight materials are also supportive of a chain growth mechanism. Ni(COD) 2 , in the presence of PPh 3 , has also been used to prepare initiators from surface-bound thienyl bromides [72]. Kiriy and coworkers have also investigated the use of external initiators containing aryl bromide groups to determine the extent of the ''ring walk'' of the associated Ni(0) catalyst (Scheme 7.11) [73].…”
Section: Initiation and Catalyst Transfer Propagationmentioning
confidence: 99%